Torsional Performance of Reinforced Concrete Beams Strengthened Using Hybrid Fibers Sifcon Jacketing - Mohammed Mohammed J.; Al-Azzawi Adel A. (Civil and Environmental Engineering)
The main aim is to investigate the influence of hybrid fiber Slurry Infiltrated Fiber Concrete (SIFCON) strengthening of beams loaded under pure torsion. The volume percentage of fiber was constant at 5%. Seven beams underwent pure torsion testing after being cast., two beams were taken as a reference (The first one without torsional reinforcement and the second beam with torsional reinforcement), and five beams were strengthened by a SIFCON jacket, One beam fully jacketed, and four beams with three-side jacket. Different types of fiber (Steel, Glass, and Hybrid) used to cast SIFCON. It found that the increase in ultimate torsion by about (163 - 537) % for strengthened beams (no torsional reinforcement) and (46 - 254)% for beams with torsional reinforcement. Finally, the fully jacket-strengthening beam with 5% from steel fiber was the most effective among strengthening beams to improve torsion strength. In addition, the results of cracking torque, twist angle, Energy Absorption (Toughness), Torsional Stiffness, and torsional strength appear enhanced when using SIFCON different types of fiber in strengthened beams.